Hyperbilirubinaemia after cardiac surgery: the point of no return - Farag, Mina; Veres, Gábor; Szabó, Gábor; Ruhparwar, Arjang; Karck, Matthias; Arif, Rawa (ESC heart failure, 2019)
Aims The occurrence of hyperbilirubinaemia after heart surgery using cardiopulmonary bypass or post-operative heart failure is fairly common. We investigated the incidence, predictive value, and post-operative outcome of hyperbilirubinaemia after cardiac surgery in an effort to identify potential risk factors and significance on clinical outcome. Methods and results Between 2006 and 2016, 1272 (10.1%) out of 12 556 patients developed hyperbilirubinaemia, defined as bilirubin concentration >3 mg/dL, during post-operative course at our institution. All patients who were operated using cardiopulmonary bypass were included. Hepatic dysfunction was diagnosed preoperatively in 200 patients (15.7%), whereas mean model of end-stage liver disease score was 11.22 ± 4.99. Early mortality was 17.4% with age [hazard ratio (HR) 1.019, 95% confidence interval (CI) 1.008-1.029; P = 0.001], diabetes (HR 1.115, CI 1.020-1.220; P = 0.017), and emergent procedures (HR 1.315, CI 1.012-1.710) as multivariate predictors. Post-operative predictors were low-output syndrome (HR 3.193, 95% CI 2.495-4.086; P < 0.001), blood transfusion (HR 1.0, CI 1.0-1.0; P < 0.001), and time to peak bilirubin (HR 1.1, CI 1.0-1.1; P < 0.001). We found an increased correlation with mortality at 3.5 post-operative day as well as an optimal cut-off value for bilirubin of 5.35 mg/dL. A maximum bilirubin of 25.5 mg/dL was associated with 99% mortality. Survival analysis showed significantly decreased survival for patients who developed late, rather than early, hyperbilirubinaemia. Conclusions Post-operative hyperbilirubinaemia is a prevalent threat after cardiopulmonary bypass, associated with high early mortality. The timing and amount of peak bilirubin concentration are linked to the underlying pathology and are predictors of post-operative outcome. Patients with late development of steep hyperbilirubinaemia warrant meticulous post-operative care optimizing cardiac and end organ functions before reaching the point of no return.
First published: 16 May 2019
Gesehen am 11.05.2020